Showrooming: fatores determinantes que impactam na intenção de compra de eletrônios e eletrodomésticos - Golin, Letícia (My University, 2019)
The use of tools for virtual research and/or acquisition provides to the customer new experiences of purchase goods. With the objective of contributing to understanding the attitude and behavior of the buyer at the time of purchase, this research seeks to identify the factors that lead Brazilian and US customers to perform electronic and home appliances search in physical stores and later acquire in virtual stores. For this, was carried out descriptive research with a quantitative approach in which were applied closed questionnaires with profile questions and questions arranged in an evaluation scale to identify factors that are important when performing Showrooming in both nationalities. After analyzing the collected data, it was possible to perceive a disparity between the perception of each nationality about the online purchases. Brazilians, in general, showed up to be withdrawn to the virtual market than the North Americans, who in turn, present greater satisfaction in performing the Showrooming. This research conducted to the result that consumers not only search to the monetary economy when searching through different sales channels but also search for the best use of time and for higher business opportunities.(sic)
A utilização de ferramentas virtuais para pesquisa e/ou compra proporciona ao consumidor novas experiências de aquisição de mercadorias. Com o objetivo de contribuir com o entendimento da atitude e comportamento do consumidor no momento da compra, esta pesquisa busca identificar os fatores que levam compradores brasileiros e estadunidenses a realizar pesquisas de eletrônicos e eletrodomésticos em lojas físicas com posterior aquisição em lojas virtuais. Para isso, realizou-se uma pesquisa descritiva, com abordagem quantitativa, na qual foram aplicados questionários validados fechados com questões de perfil do respondente e questões direcionadas. Após a análise dos dados coletados, foi percebida a disparidade entre a percepção de cada nacionalidade sobre compras on-line. Os brasileiros, de forma geral, se mostram mais retraídos ao mercado virtual do que os norte-americanos que, por sua vez, apresentam maior satisfação ao realizar showrooming. A pesquisa conduziu ao resultado de que consumidores não buscam somente economia monetária quando realizam pesquisa em diferentes canais de venda, mas visam melhor aproveitamento do tempo e oportunidades de melhores negócios.(sic)
Keywords: Comportamento do consumidor; Compras